The Effect of Angiotensin Receptor and Neprilysin Inhibitors on Quality of Life in Patients with Heart Failure with Reduced Ejection Fraction and Functional Mitral Regurgitation - A. S. Ryazanov; E. V. Shikh; O. V. Kechina; M. V. Makarovskaya; A. A. Kudryavtsev (Столичная издательская компания, 2023)
Aim. To compare the change in quality of life indicators and the main clinical and instrumental parameters in patients with chronic heart failure (CHF) and functional mitral regurgitation (FMR) under the influence of sacubitril/valsartan compared with valsartan in an outpatient practice.Material and Methods. The study included 90 patients with chronic FMR, who were observed for 12 months. They received sacubitril/valsartan or valsartan. Efficiency criteria were: the difference between groups in scores according to the Kansas questionnaire for patients with cardiomyopathy; MR degree parameters (change in effective regurgitation orifice area, vena contracta width, MR volume and MR fraction); indicators of the severity of myocardial remodeling (left ventricular EF; the level of N-terminal brain natriuretic propeptide), exercise tolerance based on a 6-minute walk test, a change in the functional class of heart failure according to NYHA.Results. In a treatment efficacy analysis, the Kansas City Cardiomyopathy Questionnaire-Overall Summary Score improved by 22.1 points in the sacubitril/valsartan group and by 4.5 points in the valsartan group (p<0.001). EF, exercise tolerance, and the number of patients transitioning from NYHA functional class III to II increased in the sacubitril/valsartan group (p<0.05). Also, in this group, the effective area of the regurgitation opening, the width of the vena contracta, the volume of regurgitation, the fraction of regurgitation, and the level of N-terminal brain natriuretic propeptide (p<0.05) decreased more pronouncedly (p<0.05).Conclusion. Compared with valsartan, treatment with sacubitril/valsartan leads to a significant improvement in the quality of life in patients with FMR and HF with reduced EF, which is largely associated with a change in NT-proBNP, echocardiographic characteristics of the severity of MR and the degree of myocardial remodeling.